1985
DOI: 10.1152/ajpheart.1985.249.2.h278
|View full text |Cite
|
Sign up to set email alerts
|

Dietary salt loading produces baroreflex impairment and mild hypertension in rats

Abstract: Mild hypertension with reduced chronotropic baroreflex sensitivity to phenylephrine occurred in Sprague-Dawley rats fed a high-salt diet for 5 wk. Progressive elevation of systolic and mean pressures, detected initially by indirect tail-cuff measurement, was later verified by direct recording of phasic pressures from indwelling aortic catheters in the same rats. Reflex bradycardia during pressor responses to phenylephrine was consistently less pronounced in salt-loaded than in control rats, whether tested whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 0 publications
5
26
0
Order By: Relevance
“…For example, dietary salt loading in normal rats impairs baroreceptor reflex control of heart rate but not renal sympathetic nerve activity. 29 More relevant to the present study, some investigators have shown that baroreceptor reflex control of renal sympathetic activity in anesthetized 2 and conscious SHR 30 is normal despite impaired regulation of the heart. Although this has not been found by all investigators, 31 the present study demonstrated that baroreceptor reflex control of heart rate in SHAM-SHR was impaired but lability of arterial pressure was not different from SHAM-WKY rats.…”
Section: Discussionmentioning
confidence: 57%
“…For example, dietary salt loading in normal rats impairs baroreceptor reflex control of heart rate but not renal sympathetic nerve activity. 29 More relevant to the present study, some investigators have shown that baroreceptor reflex control of renal sympathetic activity in anesthetized 2 and conscious SHR 30 is normal despite impaired regulation of the heart. Although this has not been found by all investigators, 31 the present study demonstrated that baroreceptor reflex control of heart rate in SHAM-SHR was impaired but lability of arterial pressure was not different from SHAM-WKY rats.…”
Section: Discussionmentioning
confidence: 57%
“…It has been reported that chronic increased sodium intake may increase blood pressure (11,22), and reducing sodium is thought to reduce blood pressure although few studies actually demonstrate this. The inability of investigators to show reductions in blood pressure due to reduced sodium intake may reflect permanent changes in the cardiovascular and renal systems that are caused by obligatory feeding of excess sodium after weaning.…”
Section: Resultsmentioning
confidence: 99%
“…Manipulation of dietary sodium intake is an important experimental paradigm for studying renal physiology or pathophysiology. High salt intake has been found to influence a wide variety of physiological parameters in otherwise normal rats, including blood pressure (7,11,17,18,22), renin secretion (2,20,21), plasma aldosterone (7,20), angiotensin receptors (20), nitric oxide synthase (2,21), cyclooxygenase (9,22), endothelin (18), insulin resistance (17), and vascular adaptation (22). Commercial "normal" rat chows contain 0.3-0.5% sodium, while experimental "high-salt" diets contain 2-8% sodium (2, 7, 11, 17, 18, 20 -22).…”
mentioning
confidence: 99%
“…For these reasons, changes in nitrergic control system [33,34] may also contribute to this type hypertension. Moreover, salt loading may impair baroreflex [35] and sympathoinhibitory response to angiotensin II-induced hypertension [11]. Such impairments in pressure control mechanisms which are dependent on local ANG II activity or No may contribute to maintaining high BP in clipped rats under salt loading.…”
Section: Renal Weightsmentioning
confidence: 99%
“…In addition, salt loading inverted the relationship between HR and cardiac autonomic activity in the clipped rats. In fact, salt dependent changes in adrenergic receptors [47] and baroreflex [35] may have caused to the changes in cardiac autonomic activity and its relationship with HR in clipped rats under salt loading. However, the salt did not significantly affect the basal HR level in the hypertensives.…”
Section: Renal Weightsmentioning
confidence: 99%